2015
DOI: 10.1007/s11832-015-0671-y
|View full text |Cite
|
Sign up to set email alerts
|

The presentation of Legg−Calvé−Perthes disease in females

Abstract: PurposeLegg−Calvé−Perthes disease (LCPD) is uncommon in girls. The presentation of LCPD in female patients has been reported as later in onset and associated with certain high-impact activities. Our aim is to characterize the presentation of female LCPD at a large center, with particular attention to the clinical and radiographic features of late-onset disease (>ten years of age). We perceived an increasing burden of late-onset disease with adult-like radiographic features.MethodsAll patients presenting to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The condition described above was diagnosed as likely being LCPD of the hip. LCPD occurs in several stages, and onset is typically between the ages of four and eight years (Georgiadis, Seeley, Yellin, & Sankar, ), although some cases do occur in early childhood and adolescence (Gill, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The condition described above was diagnosed as likely being LCPD of the hip. LCPD occurs in several stages, and onset is typically between the ages of four and eight years (Georgiadis, Seeley, Yellin, & Sankar, ), although some cases do occur in early childhood and adolescence (Gill, ).…”
Section: Resultsmentioning
confidence: 99%
“…LCPD occurs more frequently in boys than girls (Gill, , Gray, Lowry, & Renwick, , Hall, Barker, Dangerfield, & Taylor, , Kim, Hiroshima, & Imaeda, , Moberg & Rehnberg, ). When present in girls, it is associated with high impact sports or repetitive athletics (e.g., Georgiadis et al, ; Larson, Kim, & Herring, ), and animal experiments have successfully induced LCPD through repetitive activity (Zhang et al, ). However, Kim et al () found that only 14.2% of affected children were athletes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, pioneer studies on these differences reported a more severe presentation and prognosis in female patients than in male subjects[ 97 ]. However, recent high profile epidemiological studies reported no significant differences in clinical presentation, outcome and prognosis between boys and girls[ 98 , 99 ]. Thus, the LCPD male/female ratio appears not to be associated with different clinical presentation and should not be part of the clinical treatment algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…LCPD has a very variable incidence, it ranges between 0.4/100000 and 29.0/100000, and its appearance is mainly in males. Unfortunately, in our country, there is no prevalence data, but, due to its occurrence and appearance, it is considered as a low incidence disease [5][6][7]. There are multiple theories about the etiology of LCPD; however, many of them remain controversial due to lack of foundation and/or reproducibility.…”
Section: Introductionmentioning
confidence: 99%